Individual differences in working memory capacity and visual search while reading. - Redden, Ralph S.; Eady, Kaylee; Klein, Raymond M.; Saint-Aubin, Jean (Memory & Cognition, 2023)
Individual differences in working memory capacity are related to variations in a wide range of cognitive tasks. Surprisingly, effects of individual differences in working memory capacity are somewhat limited in visual search tasks. Here we tested the hypothesis that such an effect would be robust when search was one component of a dual task. Participants were presented strings of letters using rapid serial visual presentation and were required to detect all instances of a particular target letter. In Experiment 1, participants performed the letter search task in three contexts, while: (a) reading a prose passage, (b) processing a stream of random words, or (c) processing a random stream of non-words. In the absence of the dual task of reading prose, and in line with much of the literature on individual differences in working memory capacity and visual search, search performance was unaffected by working memory capacity. As hypothesized, however, higher working memory capacity participants detected more target letters than lower capacity participants in the "true" dual task (searching while reading prose). The hypothesized results from the prose passage were replicated in Experiment 2. These results show that visual search efficiency is dramatically affected by working memory capacity when searching is combined with another cognitive task but not when it is performed in isolation. Our findings are consistent with recent suggestions that visual search efficiency will be affected by working memory capacity so long as searching is embedded in a context that entails managing resource allocation between concurrent tasks.